Analisis Manajemen Bimbingan Konseling Kelompok di SMA Negeri 1 Parigi - Nadia Lutfi Magpiroh; Dede Nurhida Dehida; Riski Idul Rohman; Pajar Nurhidayah; Veni Nurpadiati (J-STAF : Siddiq, Tabligh, Amanah, Fathonah, 2024)
This research concerns the analysis of group counseling (BK) at SMA Negeri 1 Parigi. The aim of the research is to conduct an analysis of group counseling guidance management at SMA Negeri 1 Parigi. The research method used was qualitative with research subjects being three guidance and counseling teachers at SMA Negeri 1 Parigi. The research results show that group guidance and counseling services at SMA Negeri 1 Parigi are very necessary considering the absence of guidance and counseling hours in class and the large number of students. The group counseling program provides a significant positive impact, involving techniques such as problem solving and role playing. Even though there are supporting factors such as adequate facilities, experience of guidance counselors, and services via social media, there are still obstacles such as a lack of guidance counselor personnel, limited student openness, and problems with facilities and infrastructure. Evaluation of group guidance management is important, with the need for cooperation between guidance and counseling teachers, school personnel and the government. Supporting and inhibiting factors need to be managed holistically to ensure the effectiveness of the group guidance and counseling program at SMA Negeri 1 Parigi. Thus, this research is expected to provide comprehensive insight and strategic recommendations to improve the quality of Group Counseling Guidance services at SMA Negeri 1 Parigi.